Experimental investigation on the flow boiling of R134a in a multi-microchannel heat sink - Dalkilic, Ahmet Selim; Ozman, Cansu; Sakamatapan, Kittipong; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The present study reports on an experimental evaluation of flow boiling of R134a inside a multi-microchannel heat sink. The copper test section consisted of 27 parallel rectangular channels with 0.470 mm depth, 0.382 mm width, 0.416 mm fin thickness and 40 mm length. The experiments were performed at saturation temperatures of 18, 23 and 28 degrees C, mass fluxes of 800, 1000 and 1200 kg m(2) s(-1) and constant vapor quality at the heat sink inlet at 0.05. The wall heat flux was increased from 50 kW m(-2) until reaching critical heat flux, and maximum value of 460 kW m(-2) was reached. With the collected data from the experiments, the effects of mass flux, heat flux, saturation temperature and steam quality on the heat transfer coefficient are emphasized and the reasons are discussed. At low vapor quality, heat flux plays a major role in increasing the heat transfer coefficient, while the effect of mass flux is negligible. With rising heat flux, convective boiling begins to control the heat transfer mechanism, and the heat transfer coefficient increases with rising vapor quality and mass flux, until dry-out point. In all conditions, high heat transfer coefficients are obtained for high saturation temperatures. In open literature, the correlation generated by Mortada et al. for heat transfer coefficient is the one that makes the most accurate prediction for current study. Based on the experimental results, a correlation is proposed to calculate the heat transfer coefficients for R134a flow boiling inside the multi-microchannel at high mass and heat flux predicting the measured ones better than those in the literature.
Keywords: Microchannel; Boiling; Heat transfer coefficient; Wall heat flux; Heat transfer enhancement; PRESSURE-DROP; COOLING APPLICATIONS; MICRO/MINI-CHANNELS; VAPOR QUALITY; 2-PHASE FLOW; R-134A; FLUX; REFRIGERANTS; DIAMETER; TUBES; Thermodynamics; Mechanics